Predicting Cervical Alignment Required to Maintain Horizontal Gaze Based on Global Spinal Alignment. Issue 23 (1st December 2016) - Diebo, Bassel G.; Challier, Vincent; Henry, Jensen K.; Oren, Jonathan H.; Spiegel, Matthew Adam; Vira, Shaleen; Tanzi, Elizabeth M.; Liabaud, Barthelemy; Lafage, Renaud; Protopsaltis, Themistocles S.; Errico, Thomas J.; Schwab, Frank J.; et al.
Abstract : Study Design: A retrospective cohort. Objective: The aim of this study was to investigate the cervical alignment necessary for the maintenance of horizontal gaze that depends on underlying thoracolumbar alignment. Summary of Background Data: Cervical Sagittal Curve (CC) is affected by thoracic and global alignment. Recent studies suggest large variability in normative CC ranging from lordotic to kyphotic alignment. No previous studies have assessed the effect of global spinal alignment on CC in maintenance of horizontal gaze. Methods: Patients without previous history of spinal surgery and able to maintain their horizontal gaze while undergoing full body imaging were included. Patients were stratified on the basis of thoracic kyphosis (TK) into (<30, 30–40, 40–50, and >50) and then by SRS-Schwab sagittal vertical axis (SVA) modifier into (posterior alignment SVA <0, aligned 0–50, and malaligned >50 mm). Cervical alignment was assessed among SVA grade in TK groups. Stepwise linear regression analysis was applied on random selection of 60% of the population. A simplified formula was developed and validated on the remaining 40%. Results: In each TK group (n = 118, 137, 125, 197), lower CC (C2-C7) was significantly more lordotic by increased Schwab SVA grade. T1 slope and cervical SVA significantly increased with increased thoracolumbar (C7-S1) SVA. Upper CC (C0-C2) and mismatch between T1 slope and CC (T1-CL) were similar. Regression analysis revealed LL minus TK (LL-TK) as an independent predictor ( r  = 0.640, r 2  = 0.410) with formula: CC = 10- (LL-TK)/2. Validation revealed that the absolute difference between the predicted CC and the actual CC was 8.5°. Moreover, 64.2% of patients had their predicted C2-C7 values within 10° of the actual CC. Conclusion: Cervical kyphosis may represent normal alignment in a significant number of patients. However, in patients with SVA >50 and greater thoracic kyphosis, cervical lordosis is needed to maintain the gaze. Cervical alignment can be predicted from underlying TK and lumbar lordosis, which may be clinically relevant when considering correction for thoracolumbar or cervical deformity Level of Evidence: 3